Monkeypox as a potential emerging pandemic: a discussion on future risks and preparedness in Saudi Arabia - Shoaib, Haneen Mohammad (Frontiers in Public Health, 2023)
Monkeypox, a zoonotic disease caused by the Monkeypox virus, has emerged as a potential threat with pandemic potential in various regions. While it is challenging to predict specific outbreaks, understanding the factors contributing to Monkeypox’s pandemic potential is important. This discussion paper explores the future risks and preparedness measures concerning Monkeypox in Saudi Arabia. The study reviews the past and current knowledge on the Monkeypox outbreak, including its clinical presentation, transmission dynamics (animals-to-humans and humans-to-human), epidemiology, and diagnostic methods. Furthermore, it explores the potential risk factors for the spread of Monkeypox within the Gulf Cooperation Council (GCC) countries, mainly in the Saudi Arabian context, considering factors such as urbanization and travel and trade patterns. The paper emphasizes the importance of early virus detection, surveillance systems, and laboratory capacity in vaccinating and responding to Monkeypox cases. Additionally, it highlights the future risks and preparedness in Saudi Arabia and the usage of social media during the pandemic seeking support and awareness about Monkeypox, and it also highlights the need for effective communication strategies of leaders through social media channels to disseminate accurate information to the public, healthcare providers, and policymakers. The discussion concludes by calling for collaborative efforts among health authorities, researchers, and international medical partners to enhance surveillance, develop outbreak response plans, and ensure the availability of vaccines and treatment options. This research serves as a foundation for guiding future preventive measures and strengthening the overall preparedness of Saudi Arabia in facing the potential emergence of Monkeypox as a future pandemic.